Temporal snacking patterns among Canadian children and adolescents - Tugault-Lafleur, Claire; Polsky, Jane (Université d'Ottawa | University of Ottawa, 2024)
Snacking is nearly universal among children but there is growing concern around snacking patterns and energy contribution. This study aimed to characterize temporal snacking patterns among Canadian children and adolescents. A cross-sectional analysis drew on data from 5209 respondents aged 4–18 years from the 2015 Canadian Community Health Survey Nutrition, using one 24 h dietary recall. Descriptive statistics estimated proportions of morning, afternoon, and evening snackers, the mean caloric contribution of each snacking period to total daily energy intake, and the top food categories consumed as snacks (kcal per capita). Snacking was nearly universal and accounted for one of every four calories consumed. Morning snacks were more popular among children vs. adolescents and contributed significantly less energy than afternoon or evening snacking periods for both age groups (P < 0.001). The top food groups consumed as snacks were the same for children and adolescents, although the ranking order varied. Fruits were the leading food group in terms of per capita energy for children and second for adolescents. Aside from fruits and milks, all other top per capita energy contributors were generally more energy-dense, nutrient-poor foods such as cookies, biscuits and cereal bars, and other breads. Among children, morning snacks were higher in desirable nutrients compared with afternoon snacks. Not all snacking periods are equal in terms of energy and nutrients. A better understanding of how time of day may influence the quality of snack foods can inform meal-based guidance and help children achieve the recommended daily amounts of foods and nutrients.
Keywords: snacking; eating behaviours; time of day; children; adolescents; Canada